The Role of Student Organizations in Improving Arabic Language Achievement and Skills - Amelia, Amelia; Zou, Guijiao; Jie, Lie (Journal International of Lingua and Technology, 2022)
The problem that researchers get in organizations to improve Arabic skills is the lack of students who speak Arabic actively in the Institut Agama Islam Negeri Batusangkar campus environment. Where students still do not understand the rules in Arabic, especially in terms of mufradat, therefore researchers deliberately raise this as a problem in the current Institut Agama Islam Negeri Batusangkar student organization to improve student achievement and skills in Arabic. In this organization, researchers made the environment on campus into an Arabic-language environment which the organization calls Khimah Araby. Then every week, precisely on Friday morning, the student organization carries out a work program called Ihya’ul Araby. This article aims to develop b?’ahlughawiyyah conducted by the student association of the Arab Education Department of the Batusankar Islamic Institute. This research focussed on the bi’ah lughawiyyah model in terms of the purpose of bi’ah lughawiyyah, the form of activity, and the learning model of bi’ah lughawiyyah. This survey’s method is qualitative and uses the Google Forms method (questionnaire). Data analysis is carried out by questionnaire analysis. The result of this study shows that the b?’ah lughawiyyah development model is based on language learning objectives and curriculum objectives. The forms of activity are making learning modules, Nahwu Sharaf learning, Bia’ah Lughawiyyah, Ilq?’Mufrad?t, Muhadatsah, Monthly Insha’, Language Learning, Rihlah Lughawiyyah, Arts and Competitions (PARBARA). There are three learning models, namely the student learning model by the teacher, the student learning model by the tutor, and the student learning model by the student